Pengaruh Kualitas Pelayanan, Budaya Organisasi, Dan Lingkungan Kerja Terhadap Kepuasan Orang Tua Murid Di SD Yos Sudarso III Batam - Sihaloho, Asner (Tractare: Jurnal Ekonomi-Manajemen, 2023)
This study aims to determine the effect of service quality, organizational culture and work environment on the satisfaction of parents of SD Yos Sudarso III Batam students either partially or simultaneously. This research was conducted using quantitative methods, the population in this study was 352 people. Sampling used the Slovin formula with a total of 188 respondents. Data collection techniques using questionnaires and distributed via questionnaires. Data analysis used SPSS version 26. The results of the study found that the service quality variable had a tcount of 1.803 > ttable of 1.653 with a significance value of 0.000 <0.05, then H0 was rejected and Ha was accepted, organizational culture variable had a tcount of 4.755 > ttable of 1.653 and a significance value of 0.003 <0.05, then H0 is rejected and Ha is accepted. The work environment variable has a tcount of 3.470 > ttable of 1.653 and a significance value of 0.000 <0.05, then H0 is rejected and Ha is accepted. The three variables namely service quality, organizational culture and work environment together have a Fcount of 13.810 > Ftable of 2.65 and a significance value of 0.000 <0.05. This shows that simultaneously the quality of service, organizational culture and work environment have a positive and significant effect on the satisfaction of parents of SD Yos Sudarso III Batam students. The relationship between variables can be written by the equation Y = 28,496 + 0.072 X1 + 0.259X2 + 0.023X3. The effect of the independent variable on the dependent variable is 72.4% while the remaining 27.6% is influenced by other factors not examined.